Growth promotion of rapeseed (Brassica napus) associated with the inoculation of phosphate solubilizing bacteria - Valetti, Lucio; Iriarte, Liliana Beatriz; Fabra, Adriana (2018)
Inoculation of microorganisms to improve crop yields and minimize the use of chemical fertilizers is a promising sustainable strategy. The objective of this study was to isolate and identify bacteria from the rhizosphere of rapeseed plants able to solubilize phosphate and promote the growth of this crop. We isolated 40 different bacterial morphotypes which were phenotypically and genotypically characterized. Fourteen isolates (37.8%) were able to solubilize phosphate, 9 of them being epiphytic and 5 endophytic. In greenhouse experiments 7 of these isolates increased shoot dry weight, reaching values similar to those of fertilized plants. Additionally, we determined that survival, growth and biofilm formation ability of these bacteria were not affected by rapeseed root exudates. All the phosphate solubilizing strains able to promote plant growth under greenhouse conditions, with the exception of Bacillus sp. LTAD-52, also increase rapeseed yield (from 21 to 44%) in field trials.